EFL Students Strategies in the Process of Writing - Setya Resmini; Gartika Pandu Bhuana; Siska Rizkiani; Angga Maulana (Institut Agama Islam Negeri Palopo, 2024)
Writing has been taught for many years as one of the skills that need to be acquired to learn English. However, the long process of writing, which consists of pre-writing, writing, and revising stages, makes it more difficult for the students to do it. Therefore, this study aims to investigate students' strategies in the process of writing. The study used a qualitative design that employed a questionnaire as the main instrument for collecting the data. The questionnaire was distributed to 45 first-year college students. The result from the questionnaire shows that the students used some strategies in each stage of the writing process: pre-writing (70.63%), writing (72.95%), and revising (60.16%). In pre-writing, the students primarily applied resourcing and elaborating strategies. During the writing stage, the most commonly employed strategy was rereading. Finally, in the last phase, they solely employed proofreading as their strategy. By understanding the students' strategies in writing, the teacher can help them develop better writing skills as well as facilitate them in becoming more effective writers.